A Comparative Study on State of Charge Estimation using EKF and IEKF - Derouech Yassine; Mesbahi Abdelouahed (E3S Web of Conferences)
The nature of the “Portable Intelligent Micro Device for Hemodialysis” system requires a mobile electrical energy source capable of providing the essential power for efficient system operation. A battery with a management system can ensure this operation, the first target is to model the battery with a simple model capable of combining the various internal and external parameters that can affect battery behavior, then we develop the equations required to compose the two filters “Extended Kalman Filter” and “Invariant Extended Kalman Filter” in order to guarantee the estimation of the state of charge, which is a key element for the desired operation, and finally a MATLAB/Simulink simulation to compare the two filters, which reveals the IEKF filter’s performance in terms of stability and precision.